Spanish Political Parties on Facebook: New Sources of Content for Political Journalism - Dra. Ana BERIAIN BAÑARES,Dra. Raquel CRISÓSTOMO GÁLVEZ,Dr. Ismael XIVA I MOLINA (Fonseca, Journal of Communication, 2023)
Political parties take advantage of the internet to disseminate their messages, particularly during election campaigns. In addition to the public, these messages reach journalists, who have turned these platforms into another tool for their professional work. The aim of this study is to reflect on how the nature of publications can affect the work of journalists who use this content as raw material to work with.